Building cooperative learning to address alcohol and other drug abuse in Mpumalanga, South Africa: a participatory action research process. Issue 1 (31st December 2020) - Oladeinde, Oladapo; Mabetha, Denny; Twine, Rhian; Hove, Jennifer; Van Der Merwe, Maria; Byass, Peter; Witter, Sophie; Kahn, Kathleen; D'Ambruoso, Lucia
ABSTRACT: Background : Alcohol and other drug (AOD) abuse is a major public health challenge disproportionately affecting marginalised communities. Involving communities in the development of responses can contribute to acceptable solutions. Objectives : To: (1) document forms, processes, and contexts of engaging communities to nominate health concerns and generate new knowledge for action; (2) further build participation in the local health system by reflecting on and adapting the process. Methods : PAR was progressed with 48 community stakeholders across three rural villages in the MRC/Wits Agincourt Health and Socio Demographic Surveillance System (HDSS) in Mpumalanga, South Africa. A series of workshops explored community-nominated topics, systematised lived experience into shared accounts and considered actions to address problems identified. Photovoice was also used to generate visual evidence. Narrative and visual data were thematically analysed, situated within practice frameworks, and learning and adaption elicited. Results : AOD abuse was identified as a topic of high priority. It was understood as an entrenched social problem with destructive effects. Biopsychosocial impacts were mapped and related to unemployment, poverty, stress, peer pressure, criminal activity, corruption, and a proliferating number of taverns. Integrated action agendas were developed focussed on demand, supply, and harm reduction underpinned by shared responsibility among community, state, and non-state actors. Community stakeholders appreciated systematising and sharing knowledge, taking active roles, developing new skills in planning and public speaking, and progressing shared accountability processes. Expectations required sensitive management, however. Conclusion : There is significant willingness and capacity among community stakeholders to work in partnership with authorities to address priority health concerns. As a process, participation can help to raise and frame issues, which may help to better inform action and encourage shared responsibility. Broader understandings of participation require reference to, and ultimately transfer of power towards, those most directly affected, developing community voice as continuous processes within social and political environments.